(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
Abstract. The article discusses the problems associated with the formation and organization of dissertation funds in scientific libraries. Special attention is paid to the issues of acquisition, storage, and accessibility of dissertation materials as unique sources of scientific knowledge. The role of modern information technologies in improving the system of collection, preservation, and use of dissertation works is analyzed. The article also proposes ways to optimize the management of dissertation funds in order to ensure their effective functioning as an integral part of scientific information resources.